Modern heritage and the architecture of memories: a study on the castelo branco mausoleum in fortaleza - Nobre Guimarães, Lucas; Fundarò, Mario (Seven Editora, 2023)
The heritage issue, after nearly two centuries of discussion, is still full of myths and inconsistencies in keeping with the theory and practice of safeguarding assets and thematic accessibility. It is also known that the patrimony demarcates the memorial foundations of the collectivity and should serve the population from its socio-educational capacity, but, in practice, this often does not occur, resulting in the destitution of the sociocultural function of the good. The question of modern heritage makes the discussion even more ambiguous, promoting polemical debates, detaching the object from its historical value or framing its aesthetic value as mistaken. In this perspective, the choice of the object of study was based on the analysis of the set of the Palácio da Abolição and the Castelo Branco Mausoleum in Fortaleza (CE), as it is a significant landmark for the city in both a functional and formal aspect, housing the headquarters of the state government and composing a daring architectural ensemble in an important neighborhood in Fortaleza. However, looking at it in the semiological perspective of its architecture, it appears that the Mausoleum pays homage to the first president of the Brazilian dictatorial period, making it necessary, therefore, to raise a problematization related to the modern heritage and its function, under the memory architecture perspective. DOI: 10.56238/pacfdnsv1-008